Efeitos de um curso de habilidades sociais e educativas para professores via (EaD) na prevenção e combate ao bullying - Botura, Beatriz Jabor (2022)
The theoretical practical field of Social Skills is important not just only for academic development of the student, but also for your socioemotional development and prevention of externalizing and internalizing behavior problems. Among them, one that has been a matter of high concern in this century: bullying. Inserted in a replication of a distance course for teacher training, the present research aimed to evaluate the impact of the program and of one unity about bullying on the Social Skills and Social Educational Skills repertoire, your conceptions and practices of combat and prevention of bullying and on your perception of socioemotional development and academic competence of your students. Six Elementary School teachers were evaluated throughout the course, as well as six students each. The instruments used to assess the repertoire of these teachers were Social Educational Skills Inventory, Social Skills Inventory and a quiz about bullying. The Children’s Social Skills, Behavior Problems and Academic Competence Inventory were used to assess the students. Two types of analysis were made, qualitative and quantitative, the first being through the NVivo software and focused on specific data about bullying. As for the quantitative, parametric and non-parametric tests were performed and analyses with the JT method to access the participants’ social skills and social educational skills repertoires. The obtained results by the research showed statistically significant difference in the teacher’s performance in the social skills and social educational skills repertoire and knowledge about bullying and the JT method showed that for some participants these differences can be attributed to the intervention. Furthermore, it has been a significant impact of the academic competence of the evaluated students and in the factor 4 of the social skills indicator. These results demonstrate the importance of teacher training, aiming the socioemotional development of their students. Future researches with big samples and multimodal evaluations are suggested.